Application of MS bacteriophages on contaminated trimmings reduces Escherichia coli O157 and non-O157 in ground beef. (December 2020) - Shebs-Maurine, E.L.; Torres, E.S.; Yeh-Parker, Y.; de Mello, A.S.
Abstract: According to the United States Food and Drug Administration (FDA) agency, bacteriophage solutions targeting the serotype O157:H7 are Generally Recognized as Safe (GRAS) to control STEC during beef processing. However, outbreaks involving the "Big Six" STEC increased the industry concern about those serotypes. The objective of this study was to test the efficacy of MS bacteriophages to reduce the "Big Six" non-O157 STEC in beef. The lysing efficacy of phages isolated for each specific serotype varied from 96.2% to 99.9% in vitro . When applied to contaminated trim, reductions ranging from 0.7 to 1.3 Log of all STEC were observed in ground beef. Bacteriophages may provide an additional barrier against the "Big Six" STEC in ground beef. Results of this research provide support documentation to the FDA to extend GRAS status for bacteriophages as processing aids against all adulterant STEC. Highlights: Only phage solutions targeting STEC O157:H7 are allowed to be used in the U.S. Non-O157 serotypes ("Big Six") also lead to foodborne outbreaks and product recalls. Phages isolated for the "Big Six" reduce bacteria loads.